Remoção de amônia em lixiviado de aterro sanitário como estruvita - Fernando Augusto Moreira (2009)
Landfill is one of the most widely employed methods for the disposal of municipal solid waste (MSW) around the world. Up to 95 % total MSW collected is disposed of in landfills. In Brazil, this option is certainly employed in most of the cities due to the vast territorial extension and due to low operational cost in comparison to other final treatment technologies. After landfilling, solid waste undergoes physico-chemical and biological changes. Consequently, the degradation of the organic fraction of the wastes in combination with percolating rainwater leads to the generation of a highly contaminated liquid called leachate. The leachate generated in landfills is regulary pumped out and collected. It is rich in contaminants and must be treated before being discharged. This liquid is characterized by high concentration of refractory organic matter, ammonium and toxic compounds, especially in its mature stage (landfills with more than 5 years). These substances can lead to difficulties during biological treatment, being necessary to adjust the initial conditions to be favorable to specific biotic growth. A key contaminant is ammonia. High concentrations of ammonia within the leachate will be toxic to many biological treatments as ammonia is one of the major toxicants to living organisms. In order to achieve the required reductions in ammonia levels, chemical precipitation has been employed. Different precipitant agents have been used for this purpose, such as calcium hydroxide, magnesium/ammonia/phosphate - MAP (precipitation as struvite). Struvite forms an insoluble compound which can be easily separated from the liquid phase. The major problem for this technique is the high consume of salts that will provide phosphate and magnesium for the reaction, once the ideal reaction will occur under supersaturationconditions. The aim of this study is to investigate the use of industrial wastes that contain phosphate and magnesium to achieve a cost effective process. Results indicate about 76 % ammonia removal with an initial concentration of 1500 mg/L, using two industrial wastes as source of phosphate and magnesium